New-onset type 1 diabetes and severe acute respiratory syndrome coronavirus 2 infection - Anindya, Roy (2023)
Type 1 diabetes (T1D) is a condition characterized by an absolute deficiency of insulin. Loss of insulin-producing pancreatic islet β cells is one of the many causes of T1D. Viral infections have long been associated with new-onset T1D and the balance between virulence and host immunity determines whether the viral infection would lead to T1D. Herein, we detail the dynamic interaction of pancreatic β cells with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the host immune system with respect to new-onset T1D. Importantly, β cells express the crucial entry receptors and multiple studies confirmed that β cells are infected by SARS-CoV-2. Innate immune system effectors, such as natural killer cells, can eliminate such infected β cells. Although CD4+ CD25+ FoxP3+ regulatory T (TREG ) cells provide immune tolerance to prevent the destruction of the islet β-cell population by autoantigen-specific CD8+ T cells, it can be speculated that SARS-CoV-2 infection may compromise self-tolerance by depleting TREG -cell numbers or diminishing TREG -cell functions by repressing Forkhead box P3 (FoxP3) expression. However, the expansion of β cells by self-duplication, and regeneration from progenitor cells, could effectively replace lost β cells. Appearance of islet autoantibodies following SARS-CoV-2 infection was reported in a few cases, which could imply a breakdown of immune tolerance in the pancreatic islets. However, many of the cases with newly diagnosed autoimmune response following SARS-CoV-2 infection also presented with significantly high HbA1c (glycated hemoglobin) levels that indicated progression of an already set diabetes, rather than new-onset T1D. Here we review the potential underlying mechanisms behind loss of functional β-cell mass as a result of SARS-CoV-2 infection that can trigger new-onset T1D.